Zoonotic Diseases and Phytochemical Medicines for Microbial Infections in Veterinary Science: Current State and Future Perspective - Shin, Bora; Park, Woojun (Frontiers in Veterinary Science, 2018)
Diseases caused by bacterial infections in small-scale and industrial livestock are becoming serious global health concern in veterinary science. Zoonotic bacteria, including Staphylococcus, Campylobacter, and Bartonella species, that infect animals and humans cause various illnesses, such as fever, diarrhea, and related complications. Bacterial diseases in animals can be treated with various classes of antibiotics, including fluoroquinolones, beta-lactams, aminoglycosides, and macrolides. However, the overuse and misuse of antibiotics have led to drug resistance in infectious agents, e.g., methicillin-resistant Staphylococcus; this hampers the treatment of infections in livestock, and such problems are increasing worldwide. Dietary phytochemicals and herbal medicines are useful and viable alternatives to pharmaceuticals because they are economical, effective, non-resistance-forming, renewable, and environmentally friendly. They are small molecules with high structural diversity that cause selective stress to or stimulation of resident microbiota, consequently causing an abundance of such microorganisms; thus, they can be used in preventing various diseases, ranging from metabolic and inflammatory diseases to cancer. In addition, the antioxidant effects of phytochemicals prevent substantial losses in the livestock industry by increasing animal fertility and preventing diseases. Potentially effective plant extracts could be used in combination with antibiotics to decrease the required dose of antibiotics and increase their effectiveness. This strategy can help avoid the side effects of chemical antimicrobials and allow the effective use of phytochemicals for treating diseases. Furthermore, phytochemicals are considered as potential alternatives to antibiotics because of their economical, non-resistance-forming and environmentally friendly properties. Flavonoids such as resveratrol, epigallocatechin gallate, and phenols such as galangin, puerarin, and ursolic acid are proven to be effective as antimicrobial agents. This review provides invaluable information about the types of microbial infections in animals and the current knowledge on phytotherapeutic agents classified by their mode of actions. It also provides insights into potential strategies for effectively treating animal infections using phytochemicals.